Eco-friendly methoximation of aromatic aldehydes and ketones using MnCl 2.4H 2 O as an easily accessible and efficient catalyst - Ontivero, Melina C. (2021)
Fil: Fil: Ontivero, Melina C. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas; Argentina.